A Multi-Analytical Characterization of Mortars from Kathmandu (Nepal) Historical Monuments - Tsoupra, Tsoupra (2022)
The historical monuments of the ‘City of Temples’ (Kathmandu) represent an intrinsic component of Nepal’s cultural heritage. The 2015 devastating Gorkha earthquake, besides human casualties, has led to a widespread demolition or partial damage of monuments at UNESCOWorld Heritage Sites, including the ones in Durbar squares. This study, through an integrated material characterization of masonry binders, used in four case monuments from Hanuman Dhoka and Patan Durbar squares, intends to contribute to the knowledge of the technological know-how of the past in order to maintain as much as possible the original traditions and to provide appropriate conservation strategies. The analytical characterization of the ancient mortars was carried out by means of X-ray Diffraction (XRD), Attenuated Total Reflectance–Fourier Transform-Infrared Spectroscopy (ATRFTIR), Thermogravimetric Analysis (TGA), petrographic analysis, X-ray Fluorescence spectroscopy (XRF) and Pyrolysis–Gas Chromatography–Mass Spectrometry (Py-GC-MS). The composition of the mortars has been determined and is in accordance with previous research in traditional materials used in the Nepalese architecture. Chromatographic techniques proved to be particularly important in the analysis of mortars with organic binders as they revealed the possible composition of the binding media, providing additional information valuable for the future conservation/restoration of the stone monuments of the ‘City of Temples’.